UNRULY PASSENGER IN AVIATION: THE REGULATIONS AND CASES IN INDONESIA - Adya Paramita Prabandari (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Many unexpected problems can occur in aviation, whether in flights or at the airports. One of them is the existence of unruly passengers or disruptive passengers. Unruly passengers are only a minority when compared with the rest of passengers around the world. But these kinds of behaviors will bring serious consequences on the safety of other passengers and crews on board. Therefore, there must be regulations that firmly set on sanctions and punishment for the perpetrators.  The international regulations on unruly passenger are Convention on Offences and Certain Other Acts Committed on Board Aircraft signed at Tokyo on 14 September 1963, and Protocol to Amend the Convention on Offences and Certain Other Acts Committed on Board Aircraft. And the Indonesian regulations are the Act No. 2 of 1976 concerning the Ratification of the Tokyo Convention 1963, The Hague Convention of 1970, and Montreal Convention of 1971, the Penal Code (KUHP), and Act No. 1 of 2009 concerning Civil Aviation. Unruly passenger can perform any kinds of unruly/disruptive behaviors, and is taken seriously by the authorities. Because it threatened aviation safety, and also cause negative impacts, both for the airlines and for the other passengers. This resulted in huge losses for airlines, mainly in term of operational costs. As for the other passengers, this incident can cause an inconvenience feeling during the flight, and also a delay arriving at their destination.  So the perpetrators must go through legal procedures and subject to sanctions in accordance with the applicable law in Indonesia. Keywords: unruly passenger, regulations and cases in Indonesia